Beyond Oil Palm: Perceptions of Local Communities of Environmental Change - Hasanah, Nur; Komarudin, Heru; Dray, Anne; Ghazoul, Jaboury (Frontiers in Forests and Global Change, 2019)
Involving local communities in ecosystem service research can improve the relevance, quality and, ultimately, outcomes of natural resource management. Local engagement can also contribute to solutions to ecosystem management challenges by diversifying the range of options and contextualizing their applicability. The benefits to local communities of ecosystem service-based policies relative to other interventions, such as oil palm development, are, therefore, best understood from the perspectives of the local communities themselves. We used observations, focus group discussions, and interviews in four villages along the Belayan River, East Kalimantan, Indonesia, to explore how local communities in different oil palm development contexts perceive Ecosystem Services (ES). The main livelihood activity differed across these villages, which were either fishing, oil palm smallholder communities, or forest-dependent communities. Perceptions about ES varied across villages, though three services were perceived to be crucial in all four villages, namely fish provision, water quality, and land availability. These services can be a common concern entry point for discussions on landscape management. Despite common recognition of the negative impacts of oil palm development on these crucial services, all communities are nevertheless choosing to expand oil palm. Communities identified a wide array of direct and indirect drivers underlying this trend, including social influence, financial capital, ecological factors, and subsidies from local government. Early engagement of local policymakers, oil palm companies, and local communities is essential to the maintenance of crucial and widely recognized ecosystem services in oil palm landscapes